A first course in linear model theory - Ravishanker, Nalini; Chi, Zhiyi; Dey, Dipak (Chapman & Hall/CRC texts in statistical science, 2022)
A First Course in Linear Model Theory systematically presents the basic theory behind linear statistical models with motivation from an algebraic as well as a geometric perspective. Through the concepts and tools of matrix and linear algebra and distribution theory, it provides a framework for understanding classical and contemporary linear model theory. It does not merely introduce formulas, but develops in students the art of statistical thinking and inspires learning at an intuitive level by emphasizing conceptual understanding"--